2023
DOI: 10.3389/fnins.2022.1121899
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular impairments detected by optical coherence tomography angiography in multiple sclerosis patients: A systematic review and meta-analysis

Abstract: PurposeA systematic review and meta-analysis was conducted to investigate changes in retinal and choroidal microvasculature in patients with multiple sclerosis (MS) using optical coherence tomography angiography (OCTA).MethodsPubMed and Google Scholar were searched for studies that compared retinal and choroidal microvasculature between MS and healthy controls (HC) with OCTA. MS patients were divided into 2 groups: MS with (MSON) or without optic neuritis (MSNON).ResultsTotally, 13 studies including 996 MS eye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Recent reviews have indicated that thinning of the RFNL and ganglion cell layer in patients with ON is accompanied by a decrease in superficial and peripapillary capillary plexus density. [15][16][17][18] Vascular regression due to reduced metabolic demand, and endothelial damage caused by inflammation, have been proposed as potential causes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reviews have indicated that thinning of the RFNL and ganglion cell layer in patients with ON is accompanied by a decrease in superficial and peripapillary capillary plexus density. [15][16][17][18] Vascular regression due to reduced metabolic demand, and endothelial damage caused by inflammation, have been proposed as potential causes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the literature does not support this, including the authors' study. 15,25,26,29 The widening of the FAZ, and a reduction in its circularity, indicate macular ischemia. This finding is considered a marker of microvascular damage in OCTA studies, since it correlates directly with the severity of glaucoma and diabetic retinopathy, and is associated with decreased visual acuity.…”
Section: Discussionmentioning
confidence: 99%
“…OCT-Angiography (OCTA) is another novel technique that has noninvasively allowed clinicians to visualize retinal and choroidal microvasculature changes in MS patients by detecting the motion contrast of blood cells [35]. In a meta-analysis that integrated retinal and choroidal OCTA data, the superficial vascular complex (SVC) and peripapillary vessel densities were found to be significantly decreased in MS patients with or without optic neuritis relative to the control group [36]. When combined with OCT-derived metrics, OCTA data was able to improve the detection of MS without optic neuritis [8].…”
Section: The Retina As a Potential Biomarker Optical Coherence Tomogr...mentioning
confidence: 99%
“…OCT and OCTA can now be used to qualitatively and quantitatively detect the status of the retinal nerve fiber layer (RNFL), retina, and optic nerve papillae circulation. Therefore, they are currently used as clinical biomarkers for various neurological diseases ( 13 , 14 ). While previous studies on migraine hemodynamics focused on the brain using fMRI ( 15 , 16 ), several recent clinical studies have reported alterations in the retina and retinal perfusion in patients with migraine, which may provide a way to understand the ocular physiopathology observed with migraine ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%